Variation and taxonomic status of the aquatic coral snake Micrurus surinamensis (Cuvier, 1817) (Serpentes: Elapidae) - Passos, Paulo; Fernandes, Daniel S. (Zootaxa, 2005)
The taxonomic status of Micrurus surinamensis (Cuvier, 1817), is revised and variation on data concerning external morphology, osteology and hemipenis are described. Micrurus s. nattereri Schmidt, 1952 is here considered as a species, based on the number of ventral scales, shape of posterior portion of parietal bone, and length of supratemporals.